Answer:
Explanation
#1)
Step 1:
Set any equation to one variable. Let's pick the first equation.
I would make 2x-y=9 into y=2x-9.
Step 2:
Then I would subsitute 2x-9 into the (y) for the 2nd equation. The equation should look like x+3(2x-9)=-6
Step 3:
I then distribute the 3 to the 2x+9 in which the expanded form would look like x+6x-27=6
Step 4:
Then I would combine the X terms and move the -27 to the other side.
7x=33
Step 5:
I then would solve for X which is x=33/7.
Step 6:
We would plug in 33/7 for X and any of the equation whether it is the top or bottom and you should recieve your answer for Y.
#2)
Step 1:
Like #1 I would do the same, but this time let's do it for X.
I would make 2x-y=7 into x=(y+7)/2
Step 2:
I then would subsitute [(y+7)/2] into (x) for the 2nd equation below.
It should be 6[(y+7)/2]-3y=14.
Step 3:
I would then do distributive property and expand the equation.
3y+21-3y=14
Step 4:
I would then combine the Y and move the 21 over to the right side.
0y=-7
Step 5:
This shows that 0 cannot equal to 7 therefore this equation is unsolvable or we refer to as undefined.